Design of one-dimensional power spectrum using two-dimensional fast Fourier transform for discrimination of paper-based kraft tapes. (December 2015) - Sasaoka, Sara; Saito, Koichi; Higashi, Kenjirou; Limwikrant, Waree; Moribe, Kunikazu; Suzuki, Shinichi; Yamamoto, Keiji
Highlights: One-dimensional power spectrum (1D-PS) includes wavenumber and absolute intensity. The 1D-PSs enable us to compare the spectra quickly and easily. The 1D-PSs are independent from the orientation of the original images. The 1D-PSs and the improved 2D-PSs provide complementary information. The reported method is non-destructive and applicable to dirty or damaged samples. Abstract: A novel type of spectrum, the one-dimensional power spectrum (1D-PS), was designed for the discrimination of adhesive packing tapes, i.e., kraft tapes. The 1D-PS offered complementary information to that provided by the improved two-dimensional PS (2D-PS), which was calculated using our previously established image processes combined with a two-dimensional fast Fourier transform (2D-FFT) to obtain information about the spatial periodicity within kraft tapes. The 1D-PS was calculated using a three-step image process: (i) the 2D-FFT was applied to 50 randomly selected areas in a transmitted light image; (ii) the obtained 2D-PSs were accumulated without applying a logarithmic transform; (iii) the wavenumber and the maximum intensity were plotted on the x -axis and y -axis, respectively. Through an intra-roll comparison, the 1D-PSs collected from single rolls showed similar profiles. In an inter-roll comparison, the 1D-PSs from 50 commercially available brand-name products were classified into 29 groups. The 1D-PSs contained other useful information than that provided by the improved 2D-PSs: they presented more peaks and absolute intensity with a wider range. The 1D-PSs enabled us to compare the spectra quickly and easily, owing to their unchanging profiles regardless of the orientation of the scanned images. A combined use of the 1D-PSs with the improved 2D-PSs—both spectrum types being convenient, rapid, non-destructive, and applicable to dirty and/or damaged samples—could further improve the identification of kraft tapes.